Comment on "Oxygen Vacancy Ordering and Electron Localization in CeO2: Hybrid Functional Study" - Ganduglia Pirovano, Maria Veronica; Murgida, Gustavo Ezequiel; Ferrari, Valeria Paola; Llois, Ana Maria (American Chemical Society, 2017)
Fil: Ganduglia Pirovano, Maria Veronica. Consejo Superior de Investigaciones Científicas; España